Triptico. - Hoet, Jan (Gent : Snoeck-Ducaju & Zoon, 1991)
Mendes, Albuquerque ; Biberstein, Michael ; Branco, Miquel ; Burmester, Gerardo ; Cabrita Reis, Pedro ; Carvalho, Rosa ; Casqueiro, Pedro ; Chafes, Rui ; Croft, José Pedro ; Gaetan ; Lapa, Alvaro ; Portugal, Pedro ; Proença, Pedro ; Rego, Paula ; Rodrigo, Joaquim ; Sanches, Rui ; Sarmento, Julião
Triptico, Museum van Hedendaagse Kunst, Gent, 28.9.1991 - 5.1.1992
Tentoonstelling in het kader van Europalia 91 Portugal
kunstcatalogus
Keywords: Portugal